Exploring somatic mutations in BRAF, KRAS, and NRAS as therapeutic targets in Saudi colorectal cancer patients through massive parallel sequencing and variant classification - Aljuhani, Thamer Abdulhamid; Shaik, Noor Ahmad; Alqawas, Rahaf Talal; Bokhary, Rana Y.; Al-Mutadares, Mahmood; Al Mahdi, Hadiah Bassam; Al-Rayes, Nuha; El-Harouni, Ashraf AbdulRahman; Elango, Ramu; Banaganapalli, Babajan; Awan, Zuhier Ahmad (Frontiers in Pharmacology, 2024)
Background Colorectal cancer (CRC) is the leading cancer among Saudis, and mutations in BRAF, KRAS, and NRAS genes are therapeutically significant due to their association with pathways critical for cell cycle regulation. This study evaluates the prevalence and frequency of somatic mutations in these actionable genes in Saudi CRC patients and assesses their pathogenicity with bioinformatics methods. Methodology The study employed the TruSight Tumor 15 next-generation sequencing (NGS) panel on 86 colorectal cancer (CRC) samples to detect somatic mutations in BRAF, KRAS, and NRAS genes. Bioinformatic analyses of NGS sequences included variant annotation with ANNOVAR, pathogenicity prediction, variant reclassification with CancerVar, and extensive structural analysis. Additionally, molecular docking assessed the binding of Encorafenib to wild-type and mutant BRAF proteins, providing insights into the therapeutic relevance of pathogenic variants. Results Out of 86 tumor samples, 40 (46.5%) harbored somatic mutations within actionable genes (BRAF: 2.3%, KRAS: 43%, NRAS: 2.3%). Fourteen missense variants were identified (BRAF: n = 1, KRAS: n = 11, NRAS: n = 2). Variants with strong clinical significance included BRAF V600E (2.32%) and KRAS G12D (18.60%). Variants with potential clinical significance included several KRAS and an NRAS mutation, while variants of unknown significance included KRAS E49K and NRAS R102Q. One variant was novel: NRAS R102Q, and two were rare: KRAS E49K and G138E. We further extended the CancerVar prediction capability by adding new pathogenicity prediction tools. Molecular docking demonstrated that Encorafenib inhibits the V600E variant BRAF protein less effectively compared to its wild-type counterpart.